Juristes internationalistes, juristes mixtes, Euro-Lawyers : l’apport de l’expérience semi-coloniale à l’émergence d’un droit supranational - Michel Erpelding (Clio@Themis)
This paper explores the partly colonial origins of European integration law. It first notes that internationally composed and treaty-based courts with jurisdiction over individual treaty-based rights existed well before the end of WWII, notably in semi-colonial settings. It then addresses the individual careers of several jurists who circulated between Europe and countries subjected to semi-colonial domination. These careers confirm the existence of a range of continuities between international law, the mixed law applied in these countries, and post-WWII European law.